Gambaran Kesiapsiagaan Darurat Rumah Tangga Menghadapi Bencana di Kecamatan Baolan, Kabupaten Tolitoli - Novica Ariyanti Putri; Hasni Hasni; Dwi Yogyo Suswinarto (Universitas Malahayati Lampung, 2026)
ABSTRACT Indonesia is a disaster-prone country, and households serve as the frontline unit in facing disaster impacts before formal response systems intervene. Most disaster preparedness instruments used in Indonesia have been developed locally for specific hazards and have not comprehensively measured preparedness across multiple domains, including the needs of vulnerable household members. This study aimed to describe the level of household emergency preparedness in Baolan, Tolitoli Regency across five preparedness domains, including domains addressing the needs of vulnerable household members. This study used a quantitative descriptive observational design with a cross-sectional approach, conducted from June to July 2026. A sample of 100 respondents (heads of household) was selected through purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected using the Indonesian Household Emergency Preparedness Instrument (I-HEPI), comprising 50 items across five domains, with total scores converted into percentages and classified into five preparedness categories. The mean overall preparedness score was 48.3% (SD 16.0). The preparedness planning domain achieved the highest score (67.8%), while the domain addressing access and functional needs of vulnerable members achieved the lowest (41.1%), with pregnant women showing the lowest sub-criterion score (25.0%). The largest proportion of respondents (43.0%) fell into the Moderately Prepared category. Household preparedness is uneven across domains: planning-related preparedness is best mastered, whereas domains dependent on financial resources, regulatory support, and the specific needs of vulnerable members remain lagging. Cognitive domains are shaped mainly by household knowledge, while resource-dependent and conditional domains are shaped by structural factors beyond household control. These findings can guide community nurses in designing preparedness interventions tailored to each domain rather than a uniform approach. Keywords: Disaster Preparedness, Household, Community Nursing, Disaster Nursing. ABSTRAK Indonesia merupakan negara rawan bencana, dan rumah tangga berperan sebagai unit terdepan dalam menghadapi dampak bencana sebelum sistem respons formal bekerja. Sebagian besar instrumen kesiapsiagaan bencana yang digunakan di Indonesia dikembangkan secara lokal untuk bahaya spesifik dan belum mengukur kesiapsiagaan secara komprehensif pada berbagai domain, termasuk kebutuhan anggota rumah tangga yang rentan. Penelitian ini bertujuan mengetahui gambaran tingkat kesiapsiagaan darurat rumah tangga di Kecamatan Baolan, Kabupaten Tolitoli pada lima domain kesiapsiagaan, termasuk domain yang menyasar kebutuhan anggota rumah tangga yang rentan. Penelitian ini menggunakan desain deskriptif observasional dengan pendekatan cross-sectional, dilaksanakan pada Juni–Juli 2026. Sampel sebanyak 100 responden (kepala keluarga) dipilih dengan teknik purposive sampling berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Data dikumpulkan menggunakan Indonesian Household Emergency Preparedness Instrument (I-HEPI) yang terdiri atas 50 item dalam lima domain, dengan skor total dikonversikan ke bentuk persentase dan diklasifikasikan ke dalam lima kategori kesiapsiagaan. Rerata skor kesiapsiagaan keseluruhan sebesar 48,3% (SD 16,0). Domain perencanaan kesiapsiagaan memperoleh skor tertinggi (67,8%), sedangkan domain akses dan kebutuhan fungsional kelompok rentan memperoleh skor terendah (41,1%), dengan sub-kriteria ibu hamil menunjukkan skor terendah (25,0%). Proporsi responden terbesar (43,0%) berada pada kategori Cukup Siap. Kesiapsiagaan rumah tangga tidak merata pada seluruh domain: aspek perencanaan paling baik dikuasai, sedangkan domain yang bergantung pada sumber daya finansial, dukungan regulasi, dan kebutuhan kelompok rentan masih tertinggal. Domain kognitif lebih dipengaruhi pengetahuan keluarga, sedangkan domain sumber daya dan kondisional lebih dipengaruhi faktor struktural di luar kendali keluarga. Temuan ini dapat menjadi dasar bagi perawat komunitas dalam merancang intervensi kesiapsiagaan yang disesuaikan dengan karakteristik masing-masing domain. Kata Kunci: Kesiapsiagaan Bencana, Rumah Tangga, Kelompok Rentan, Keperawatan Komunitas, Keperawatan Bencana.